Phytoremediation of hypersaline soils by salt excretory C4 halophytic pan dropseed grass (Sporobolus ioclados Nees ex Trin.) through alteration in foliar architecture - Nargis Naz; Syed Mohsan Raza Shah; Sana Basharat; Mansoor Hameed; Sana Fatima; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Zaheer Abbas; Khawaja Shafique Ahmad; Abeer Hashem; Graciela Dolores Avila-Quezada; et al. (Scientific Reports)
Abstract Plants inhabiting saline areas develop specific morpho-anatomical and physiological features to survive. Sporobolus ioclados is among the few grass species that dominate highly saline habitats. This is a salt excretory species and can potentially be important for phytoremediation of salt-affected lands. Three ecotypes of Sporobolus ioclados (Trin.) Nees (DF-Derawar Fort (LSE), BD-Bailahwala Dahar (MSE), LS-Ladam Sir) from the Cholistan Desert were evaluated to investigate structural and functional modifications for salt tolerance under controlled conditions in hydroponic growth medium using half-strength Hoagland’s nutrient solution. Three salinity (NaCl) treatments were provided, namely 0 (control), 150, and 300 mM. All three ecotypes showed different structural and physiological modifications under salinity stress. Structural and functional traits were more developed in the HSE. Modifications. Structural features include intensity of sclerification and thicker leaves. Functional features were high concentration of toxic ions excretion, organic osmolytes accumulation, and maintenance of leaf turgor, photosynthesis and water use efficiency. All these confer it an excellent material for the phytoremediation as well as revegetation of highly saline lands.